Isobutyryl‐CoA dehydrogenase deficiency associated with autism in a girl without an alternative genetic diagnosis by trio whole exome sequencing: A case report. Issue 2 (11th January 2021) - Eleftheriadou, Maria; Medici‐ van den Herik, Evita; Stuurman, Kyra; van Bever, Yolande; Hellebrekers, Debby M. E. I.; van Slegtenhorst, Marjon; Ruijter, George; Barakat, Tahsin Stefan
Abstract: Background: Isobutyryl‐CoA dehydrogenase (IBD) is a mitochondrial enzyme catalysing the third step in the degradation of the essential branched‐chain amino acid valine and is encoded by ACAD8 . ACAD8 mutations lead to isobutyryl‐CoA dehydrogenase deficiency (IBDD), which is identified by increased C4‐acylcarnitine levels. Affected individuals are either asymptomatic or display a variety of symptoms during infancy, including speech delay, cognitive impairment, failure to thrive, hypotonia, and emesis. Methods: Here, we review all previously published IBDD patients and describe a girl diagnosed with IBDD who was presenting with autism as the main disease feature. Results: To assess whether a phenotype‐genotype correlation exists that could explain the development or absence of clinical symptoms in IBDD, we compared CADD scores, in silico mutation predictions, LoF tolerance scores and C4‐acylcarnitine levels between symptomatic and asymptomatic individuals. Statistical analysis of these parameters did not establish significant differences amongst both groups. Conclusion: As in our proband, trio whole exome sequencing did not establish an alternative secondary genetic diagnosis for autism, and reported long‐term follow‐up of IBDD patients is limited, it is possible that autism spectrum disorders could be one of the disease‐associated features. Further long‐term follow‐up is suggested in order to delineate the full clinical spectrum associated with IBDD. Abstract : Here, we review the clinical and molecular literature of Isobutyryl‐CoA dehydrogenase deficiency (IBDD) and present a novel case that was presenting with severe autism as the main disease feature. As extensive genetic analysis including trio whole exome sequencing did not establish a secondary cause for autism in this individual, and current reported follow‐up of IBDD individuals is limited, this case report might indicate that autism can be one of the IBDD manifestations.